The fiercest debate : Cecil A, Wright, the Benchers, and legal education in Ontario 1923-1957 - Kyer, C., Ian (Heritage., 1987)
The Law Society of Upper Canada adhered to the traditions of English legal practice and education. In the 1930s and 1940s, however, some of those traditions were challenged in a bitter debate about the nature of legal education in Ontario. This book tells the story of that debate and one of its leading participants, Cecil Augustus Wright.